Computer Aided Modeling and Analysis of Five-Phase PMBLDC Motor Drive for Low Power High Torque Application. (23rd July 2014) - Inayathullaah, M. A.; Anita, R.
Abstract : In order to achieve high torque at low power with high efficiency, a new five-phase permanent magnet brushless DC (PMBLDC) motor design was analyzed and optimized. A similar three-phase motor having the sameD / L ratio (inner diameter (D ) and length of the stator (L )) is compared for maximum torque and torque ripple of the designed five-phase PMBLDC motor. Maxwell software was used to build finite element simulation model of the motor. The internal complicated magnetic field distribution and dynamic performance simulation were obtained in different positions. No load and load characteristics of the five-phase PMBLDC motor were simulated, and the power consumption of materials was computed. The conformity of the final simulation results indicates that this method can be used to provide a theoretical basis for further optimal design of this new type of motor with its drive so as to improve the starting torque and reduce torque ripple of the motor.